Local consensus processes: effects on professional practice and health care outcomes - Nasser, Mona (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review addresses the following question: Are local consensus processes effective in improving professionals' practice or health care outcomes? To answer this question we will consider the comparisons listed below. (1) Any intervention in which local consensus processes are a component compared to no intervention. The primary aim of this analysis will be to explore heterogeneity, including potential differences between the effects of local consensus processes alone and local consensus processes as a component of multifaceted interventions. The main explanatory factors that we will consider are: the type of intervention (local consensus processes or multifaceted interventions that included local consensus processes); the contribution of local consensus processes as a component of the intervention for multifaceted interventions; setting of care (primary versus hospital); complexity of the targeted behaviour; seriousness of the outcome; baseline compliance; study quality (high or moderate protection against bias). (2) Local consensus processes compared to no intervention. (3) Any intervention in which local consensus processes is a component compared to local consensus processes alone. (4) Local consensus processes (alone or as a component) compared to other interventions. (5) Comparison of different types of local consensus processes. (6) Comparison of formal and informal local consensus process